Assessment of Emergency Department Antibiotic Discharge Prescription Dosing Errors for Pediatric Patients in a Community Hospital Health System. Issue 7 (July 2020) - Barstow, Linda; Herman, Erika; Phillips, Heidi; Maloney, Patrick
Abstract : Objectives: We quantify and describe emergency department antibiotic discharge prescription dosing errors for pediatric patients in a community hospital health system. Methods: This was a retrospective chart review evaluating emergency department discharge prescriptions written between July 1, 2014, and June 30, 2015. Pediatric patients who received a prescription for an oral antibiotic were included in error analysis if they had a weight updated in the electronic medical record during the encounter. We used a predefined threshold of +10% variance from the recommended dose to quantify error. Prescriber, environmental, and antibiotic specific data were also collected to identify variables associated with high incidence of error. Results: Among the 1934 prescriptions included in our error analysis, we detected 776 (40%) dosing errors. Of the prescriptions reviewed, 288 (15%) contained an overdosing error and 488 (25%) contained an underdosing error. There were 208 underdosing errors written for amoxicillin to treat acute otitis media. These errors represented 43% of the total underdosing errors and had a greater magnitude of variance from the recommended dose compared with overall underdosing errors. Conclusions: Underdosing of amoxicillin in acute otitis media was a dosing error that occurred frequently throughout our community health system. Further research is needed to identify the clinical impact these errors have on pediatric patients. Abstract : Supplemental digital content is available in the text.